Search and sequence analysis tools services from EMBL-EBI in 2022. Issue Volume 50:Issue W1(2022) (12th April 2022) - Madeira, Fábio; Pearce, Matt; Tivey, Adrian R N; Basutkar, Prasad; Lee, Joon; Edbali, Ossama; Madhusoodanan, Nandana; Kolesnikov, Anton; Lopez, Rodrigo
Abstract: The EMBL-EBI search and sequence analysis tools frameworks provide integrated access to EMBL-EBI's data resources and core bioinformatics analytical tools. EBI Search (https://www.ebi.ac.uk/ebisearch ) provides a full-text search engine across nearly 5 billion entries, while the Job Dispatcher tools framework (https://www.ebi.ac.uk/services ) enables the scientific community to perform a diverse range of sequence analysis using popular bioinformatics applications. Both allow users to interact through user-friendly web applications, as well as via RESTful and SOAP-based APIs. Here, we describe recent improvements to these services and updates made to accommodate the increasing data requirements during the COVID-19 pandemic. Graphical Abstract: